New device for transrectal trocar placement and rectal sealing for NOTES: a porcine in vivo and human cadaver study - Senft, Jonas; Gath, Philip; Dröscher, Tilman; Müller, Philip C.; Carstensen, Benedict; Nickel, Felix; Müller, Beat P.; Linke, Georg R. (Surgical endoscopy and other interventional techniques, 2016)
To date, hybrid NOTES, combining transvaginal and laparoscopic access, represents the most popular clinically applied NOTES approach enabling surgical handling comparable to laparoscopic surgery. The transrectal route could be used in a similar way; however, suitable devices facilitating feasible transrectal access and rectal sealing are lacking.
Gesehen am 05.05.2020